Samodzielność jednostek samorządu terytorialnego w organizowaniu usług publicznych - Kokocińska, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
Considerations taken within the article relate to the scope of autonomy of local government units in the organisation of public services, both in respect of their legal determination, which means laws binding the authorities organising the provision of services in connection with the execution of public tasks, as well as determinants of extra-legal nature. The practice of public administration shows that in addition to legal considerations, incentives of an economic nature should also be taken into account, as well as requirements resulting from the assumptions of administrative policy.Both the EU institutions and national authorities implementing the adopted policies of socio-economic development support acertain type of behaviour of public and private entities, thus creating asystem of incentives for activities consistent with the policies of the executive. This does not mean that the bodies of local government units do not have autonomy to choose the “formula” of performance of apublic task. Their decision concerning the method of performing apublic task is however often influenced by additional benefits offered, such as obtaining additional financial support from the EU funds for the implementation of public tasks in the hybrid formula of a public-private partnership. The stressed need of creating partnerships, development of cooperation between the private and public sectors, is currently dictated primarily by issues of economic nature. On the one hand, these are the restrictions of public funds to cover investment needs, and on the other — the need to improve the quality and efficiency of public services.
Keywords: jednostki samorządu terytorialnego; samodzielność; usługi publiczne; zasada partnerstwa